Application of general invariance relations reduction method to solution of radiation transfer problems. (November 2016) - Rogovtsov, Nikolai N.; Borovik, Felix
Abstract: A brief analysis of different properties and principles of invariance to solve a number of classical problems of the radiation transport theory is presented. The main ideas, constructions, and assertions used in the general invariance relations reduction method are described in outline. The most important distinctive features of this general method of solving a wide enough range of problems of the radiation transport theory and mathematical physics are listed. To illustrate the potential of this method, a number of problems of the scalar radiative transfer theory have been solved rigorously in the article. The main stages of rigorous derivations of asymptotical formulas for the smallest in modulo elements of the discrete spectrum and the eigenfunctions, corresponding to them, of the characteristic equation for the case of an arbitrary phase function and almost conservative scattering are described. Formulas of the same type for the azimuthal averaged reflection function, the plane and spherical albedos have been obtained rigorously. New analytical representations for the reflection function, the plane and spherical albedos have been obtained, and effective algorithms for calculating these values have been offered for the case of a practically arbitrary phase function satisfying the Hölder condition. New analytical representation of the «surface» Green function of the scalar radiative transfer equation for a semi-infinite plane-parallel conservatively scattering medium has been found. The deep regime asymptotics of the "volume" Green function has been obtained for the case of a turbid medium of cylindrical form. Highlights: Main features of the general invariance relations reduction method are presented. Classical asymptotics of reflection and transmission functions are exactly based. New analytical formulas for reflection function, plane and spherical albedo. Effective algorithm of calculating reflection function and albedo. Deep asymptotics of Green function for medium of cylindrical form.